2020
DOI: 10.1021/acscatal.9b05144
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Carbonylation of Dimethyl Ether on the Stable Seed-Derived Ferrierite

Abstract: The higher catalytic activity and stability for a gas-phase carbonylation of dimethyl ether (DME) to methyl acetate (MA) on the seed-derived ferrierite (FER) were attributed to its higher crystallinity with small amounts of defect sites by recrystallization methods without using any organic structure directing agent. The recrystallized FER (FER-S1) with its smaller amount of Lewis acidic extraframework Al sites (EFAl) possessed proper number of Brønsted acidic sites in the eight-membered-ring (8-MR) channels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 58 publications
2
25
0
Order By: Relevance
“…They concluded that the surface acetyl serves as the primary methylating agent toward hydrocarbon pool in zeotypes. Indeed, the relatively stable surface acetyl species are readily detected by solid-state 13 C NMR and FT-IR spectroscopy as the intermediate during the MTO , and DME/methanol carbonylation. , Acylium ion (CH 3 CO + ) may be formed during the acid-catalyzed reaction through interactions between the acylating agent (CH 3 COCl) and the Brønsted acid sites or via adsorption of CH 3 COCl in Lewis acidic AlCl 3 catalyst . The surface acetyl, rather than acylium ion, have been reported as the reactive intermediate species in both Friedel–Crafts acylation over H-Beta and Koch-type carbonylation over H-MOR zeolites up to date .…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the surface acetyl serves as the primary methylating agent toward hydrocarbon pool in zeotypes. Indeed, the relatively stable surface acetyl species are readily detected by solid-state 13 C NMR and FT-IR spectroscopy as the intermediate during the MTO , and DME/methanol carbonylation. , Acylium ion (CH 3 CO + ) may be formed during the acid-catalyzed reaction through interactions between the acylating agent (CH 3 COCl) and the Brønsted acid sites or via adsorption of CH 3 COCl in Lewis acidic AlCl 3 catalyst . The surface acetyl, rather than acylium ion, have been reported as the reactive intermediate species in both Friedel–Crafts acylation over H-Beta and Koch-type carbonylation over H-MOR zeolites up to date .…”
Section: Introductionmentioning
confidence: 99%
“…previously calcined at 550 °C for 6 h was applied as a starting material (denoted as CFER). According to the previous reports, ,, the commercial FER seed was mixed with the solution composed of SiO 2 /NaAlO 2 /NaOH/water = 1.0:0.096:0.15:36 (molar ratio) with 24 wt % of the commercial FER seed based on a total weight of FER. After a vigorous mixing of the above solution, a hydrothermal synthesis was carried out at 160 °C for 4 days, followed by filtering, washing, and drying in an oven overnight.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…However, precisely because of the specific spatial conformation of reactant DME and product MA, there is a serious limitation in exploiting/designing zeolite catalysts for such carbonylation reaction. At present, the generally accepted high-performance zeolite catalysts in carbonylation of DME to MA are H-MOR and H-ZSM-35. Nevertheless, the occurrence of the MTO side reaction in 12-MR of H-MOR causes a rapid carbon deposition, which leads to a serious deactivation of this catalyst. , By contrast, H-ZSM-35, which has the 10-MR and 8-MR as the mass-transfer channel and reaction location, respectively, performs better reaction stability due to the lighter carbon deposit in smaller 10-MR . Recently, a EU-12 zeolite demonstrated the ability to achieve carbonylation of DME with a better stability .…”
Section: Introductionmentioning
confidence: 99%